Improving of the decision-making model in the processes of external quality assurance of higher education - Fesenko, Tetiana; Ruban, Igor; Karpenko, Kateryna; Fesenko, Galyna; Kovalenko, Andriy; Yakunin, Anatolii; Fesenko, Hryhorii (Eastern-European Journal of Enterprise Technologies, 2022)
The peculiarities of external quality assurance processes in the higher education management system are considered. It is noted that the quality of educational programs (EP) of higher education institutions is controlled by quality assurance agencies (QAAs) using an accreditation system. The key features of the accreditation process in terms of peer review are identified. The problem of accreditation process management, namely the subjectivity and lack of consistency of expert decisions, is highlighted. The correlation method was applied to determine the interdependencies in expert assessments (competence, meaningful orientation of judgments, and perception of the linguistic rating scale). The identified types of variables make it possible to explain the existing measure of subjectivity that affects the collective conclusion of experts. A comprehensive methodology for quantitative evaluation of the EP quality under conditions of uncertainty based on the relative importance of the relevant criteria and subcriteria, as well as the levels of expert competence using the apparatus of fuzzy mathematics, is proposed. A basic model for the formation of a collegial expert opinion on the EP quality has been developed using the example of a system of quality criteria approved by the Ukrainian QAA. Variations in the expert values of the weight coefficients and parameters of fuzzy numbers in the context of the linguistic rating scale (“A – B – E – F”) made it possible to use the means of a computational experiment. The application of this model will allow managers to positively influence the existing ambiguity of the assessment method, which requires being guided by standard criteria and at the same time determining the EP innovativeness. In general, the application of the proposed evaluation tools on the quality of EP allows experts and managers to make decisions at a higher level of academic and managerial culture.